Anti-CD20 B Cell Treatment for Relapsing Multiple Sclerosis - Roach, Charles A.; Cross, Anne H. (Frontiers in Neurology, 2021)
Several clinical trials have demonstrated the efficacy of lytic therapies targeting B cells in the treatment of relapsing multiple sclerosis (MS). More modest efficacy has been noted in the primary progressive subtype of MS. Clinical success has increased interest in the role of B cells in the pathogenesis of MS and in ways to potentially improve upon current B cell therapies. In this mini review, we will critically review previous and ongoing clinical trials of anti-CD20 monoclonal antibodies in MS, including rituximab, ocrelizumab, ofatumumab and ublituximab. Side effects and adverse event profiles will be discussed. Studies examining the proposed mechanisms of action of B cell depleting therapies will also be reviewed.